2 sonates pour le piano par Beethoven. Oeuvre 14 ... No. [2] - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (France; Paris; S. Richault, 2023)
Early edition of the Piano Sonata no. 10 in G major, op. 14, no. 2, published in Paris by S. Richault.